2010
DOI: 10.1111/j.1468-1293.2010.00825.x
|View full text |Cite
|
Sign up to set email alerts
|

Second‐line treatment in the Malawi antiretroviral programme: high early mortality, but good outcomes in survivors, despite extensive drug resistance at baseline*

Abstract: Objectives The Malawi antiretroviral therapy (ART) programme uses the public health approach to identify ART failure. Advanced disease progression may occur before switching to second-line ART. We report outcomes for patients evaluated and initiated on second-line treatment in Malawi. Methods Patients meeting Malawi immunological or clinical criteria for ART failure in two large urban ART clinics were evaluated for virological failure (viral load >400 HIV-1 RNA copies/mL) and, if failure was confirmed, initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
87
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 30 publications
15
87
1
Order By: Relevance
“…22 A study from Malawi has shown a high rate (85%) of virological suppression on second-line ART despite extensive NRTI resistance. 23 In our study, over half of the patients, including those with complex DRMs, achieved virological suppression on second-line ART. Despite these relatively favorable on-treatment outcomes, a study of PI monotherapy after failure of an NNRTI-based regimen revealed a high incidence of low-level viremia.…”
Section: Discussionmentioning
confidence: 97%
“…22 A study from Malawi has shown a high rate (85%) of virological suppression on second-line ART despite extensive NRTI resistance. 23 In our study, over half of the patients, including those with complex DRMs, achieved virological suppression on second-line ART. Despite these relatively favorable on-treatment outcomes, a study of PI monotherapy after failure of an NNRTI-based regimen revealed a high incidence of low-level viremia.…”
Section: Discussionmentioning
confidence: 97%
“…Despite the unavailability of VL in remote areas in Senegal, HIV-1 infected patients were followed using VL testing in the main site in the capital city. Our results shows a high rate of VF (82.7%) during the first line ART as previously described in Nigeria [13], which was the main reason for switching of line regimen [14,15]. However, our data showed nine patients switched to second line regimen with three without VL testing and six with plasma viral load below 3 log 10 copies/ml.…”
Section: Discussionmentioning
confidence: 43%
“…Nonetheless, responses to second-line therapy in RLS have been favorable to date, with approximately 78% to 88% of second-line initiators alive and on treatment at the end of 1 year [19,22,33]. Even in the Malawian setting with high-level NRTI resistance, virologic suppression rates were 70% overall and exceeded 85% among survivors at the end of 1 year on second-line therapy [22]; long-term follow-up of this cohort has not yet been reported. Such favorable response is likely due to the potency of boosted protease inhibitors that have shown substantial activity among protease inhibitor-naïve patients, even as monotherapy [34][35][36][37].…”
Section: Resistance Implications Of Monitoring Strategiesmentioning
confidence: 88%
“…Risk factors for death included being identified as clinical failure or having a body mass index <18.5. Likewise, having CD4 count <50 cells/µL was associated with increased risk for death or AIDS progression [22].…”
Section: Switching To Second-line Treatmentmentioning
confidence: 99%